Radio – platforma audialna - Hopfinger, Maryla (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Almost one hundred years ago radio introduced mediated aurality to social communications. This revealed the aural dimension of culture and itself became a powerful part of the audiosphere. This democratised access to cultural values. It developed thanks to technical innovations, creating its own traditions. This involved aural perception and familiarity with its programmes’ rules. It created new literary practices, which gave birth to aural literature. It can be used both as a tool of propaganda, as well as for artistic practices. It operates in both fiction and non-fiction. In the age of the digital reconfiguration of culture, it retains its individuality as an aural means of communication. It is capable of establishing an intense contact with the public, an example of which is two models of ties with listeners: Radio Maryja and Trójka.